Gene identification, expression analysis, and molecular docking of SAT and OASTL in the metabolic pathway of selenium in Cardamine hupingshanensis - Yushan Chen; Yao Li; Guoqiang Luo; Cihang Luo; Zhijing Xiao; Yanke Lu; Zhixin Xiang; Zhi Hou; Qiang Xiao; Yifeng Zhou; Qiaoyu Tang (Plant Cell Reports, 2024)
Key message Identification of selenium stress-responsive expression and molecular docking of serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) in Cardamine hupingshanensis. Abstract A complex coupled with serine acetyltransferase (SAT) and O -acetyl serine (thiol) lyase (OASTL) is the key enzyme that catalyzes selenocysteine (Sec) synthesis in plants. The functions of SAT and OASTL genes were identified in some plants, but it is still unclear whether SAT and OASTL are involved in the selenium metabolic pathway in Cardamine hupingshanensis . In this study, genome-wide identification and comparative analysis of ChSAT s and ChOASTL s were performed. The eight ChSAT genes were divided into three branches, and the thirteen ChOASTL genes were divided into four branches by phylogenetic analysis and sequence alignment, indicating the evolutionary conservation of the gene structure and its association with other plant species. qRT-PCR analysis showed that the ChSAT and ChOASTL genes were differentially expressed in different tissues under various selenium levels, suggesting their important roles in Sec synthesis. The ChSAT1;2 and ChOASTLA1;2 were silenced by the VIGS system to investigate their involvement in selenium metabolites in C. hupingshanensis . The findings contribute to understanding the gene functions of ChSAT s and ChOASTL s in the selenium stress and provide a reference for further exploration of the selenium metabolic pathway in plants.